Development of mini pilot fluidized bed gasifier for industrial approach: Preliminary study based on continuous operation - Suksuwan, Wasu; Wae-Hayee, Makatar; Mel, Maizirwan (Penerbit Akademia Baru, 2018)
A small pilot scale of bubbling fluidized bed gasifier was designed and fabricated. The diameter of reactor (D) is 20 cm and the total height of the reactor from the bottom end of the cone to the top is 160 cm. The feedstock used was palm kernel cake which the size range of 1-10 mm. The mass feeding rate of feedstock was fixed at 0.05 kg/min, and flow rate of air was varied according to Equivalent Ratio (ER) at 0.03, 0.06, 0.19, 0.31, 0.49, 1.17, 1.43 and 2.64, respectively. In the first phase of this work is to focus on continuous gasification operation that expected approximately for 8 hours without shut down or malfunction. Based on the result obtained in this study, it was found that the ER which can be provided for continuous operation was 0.19≥ER≥1.17. For the syngas production study at the ER of 0.06 and 1.43 could not run continuously. Moreover, the gasification run at ER=0.03 and 2.64 was found that the syngas production was incombustible.